Econotronics - Popov, Evgeny Vasilyevich (Economy of Regions, 2018)
For the economic description of the social driving forces in modern society at the regional level, the author offers his concept of econotronics. It is considered as a section of social sciences, which is focused on the dynamics of the development of economic institutions of interaction between actors and society in the digital economy. The initial data used for the research are the investigations of foreign scientists and the author’s findings. The subject matter of the research is the forces driving the development of the public sector of the economy. The purpose of this study is to develop the principles and ideas of institutional modeling of the processes of public goods production in the framework of the author’s conception of econotronics. It is shown that the successful development of modern public goods is determined by network interactions between economic agents of the public sector. Institutional simulation of the production of local public goods should be based on the matrix of the current state in the coordinates of the «dynamics of the number of consumers - the dynamics of financing.» The rapid development of modern social projects depends on the application of advanced economic tools such as social innovation, crowdfunding, fundraising, etc. The development of social entrepreneurship is provided by formal and informal economic institutions adopted in the society. Creation of social innovations begins with the idea of potential innovators of how to solve a social problem, then moves to the development of a socially innovative project and concludes by the approbation of the project by the society. The establishment of the institutional atlas determines the role and place of social innovation projects in addressing market failures in social services. Economic efficiency of the implementation of a social project depends on the implementation of the commercial and public benefits. This efficiency can be determined within the matrix of the performance evaluation of social innovations. The obtained results give the opportunity for a comprehensive institutional modeling of the public sector in modern conditions to predict the further development of its driving forces.